Religious culture in modern Mexico - Nesvig, Martin Austin, 1968- (Lanham, Md. : Rowman & Littlefield Publishers, 2007)
"This book considers the role of religion and religiosity in modern Mexico, breaking new ground with an emphasis on popular religion and its relationship to politics. The contributors highlight the multifaceted role of religion, illuminating the ways that religion and religious devotion have persisted and changed since Mexican independence. They explore such themes as the relationship between church and state, the resurgence of religiosity and religious societies in the post-reform period, the religious values of the liberals of the 1850s, and the ways that popular expressions of religion often trumped formal and universal proscriptions, focusing on individual stories and vignettes and on local elements of religion, the contributors show that despite efforts to secularize society, religion continues to be a strong component of Mexican culture. Portraying the complexity of religiosity in Mexico in the context of an increasingly secular slate, this hook will be invaluable for all those interested in Latin American history and religion."--BOOK JACKET.
Miserables and citizens: Indians, legal pluralism, and religious practice in early republican Mexico / Matthew D. O'Hara -- "Para formar el corazon religioso de los jovenes": processes of change in collective religiosity in nineteenth-century Oaxaca / Daniela Traffano -- Mexican laywomen spearhead a Catholic revival: the Ladies of Charity, 1863-1910 / Silvia Marina Arrom -- Liberal religion: the schism of 1861 / Pamela Voekel -- Priests and caudillos in the novel of the Mexican nation / Alejandro Cortazar -- "A new political religious order": church, state, and workers in Porfirian Mexico / Mark Overmyer-Velazquez -- Rights, rule, and religion: Old Colony Mennonites and Mexico's transition to the free market, 1920-2000 / Jason Dormady -- Visions of women: revelation, gender, and Catholic resurgence / Edward Wright-Rios -- Juan Soldado: the popular canonization of a confessed rapist-murderer / Paul J. Vanderwood -- Religion and the Mexican revolution: toward a new historiography / Adrian Bantjes.
Includes bibliographical references (p. 255-259) and index.
Description based on print version record.
Keywords: Mexico -- Religious life and customs; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Electronic books